The Binary Opposition in Resistance Poetry: a Structuralist Analysis of PBSI Regular E'23 - Ropik Irpani; Rohanda Rohanda; R. Edi `Komarudin (UIN Sunan Gunung Djati Bandung, 2025)
This study explores the representation of binary oppositions in a resistance-themed poetry anthology composed by students of PBSI Reguler E’23, employing structuralism as the principal analytical framework. Often underestimated as amateur works, student poems in this research are positioned as ideological expressions enriched with complex symbolic structures. Drawing from Claude Lévi-Strauss’s structuralist theory, this study examines how pairs of opposing concepts—such as light vs darkness, people vs rulers, and voice vs silence—are constructed to reinforce critical messages against oppressive socio-political realities. Utilizing a descriptive qualitative approach and document analysis method, 38 selected poems were examined through an in-depth textual interpretation of diction patterns, symbolism, and narrative structures that signify ideological tension. The findings reveal that binary oppositions serve not only as stylistic elements but also as thematic foundations that articulate resistance, identity, and collective awareness among students toward social injustice. These results affirm that student poetry embodies both aesthetic and political values, deserving recognition in contemporary literary discourse. Theoretically, this study contributes to the development of structuralist approaches in modern Indonesian literary studies; practically, it offers valuable insight for literature education based on ideological critique within the university context.